2002
DOI: 10.1016/s1010-7940(02)00467-0
|View full text |Cite
|
Sign up to set email alerts
|

Invasive pulmonary aspergillosis: effects of early resection in a neutropenic rat model

Abstract: In this rat model of localized invasive pulmonary aspergillosis effects of early resection on survival could be demonstrated only in animals not receiving amphotericin B treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…None of them had undergone lung resection. We and others have previously shown that early lung resection (lobectomy or wedge resection) combined with antifungal therapy is safe, effective, and diagnostic in neutropenic patients suspected of having IPA (1,6,7,8,16,18,26). A positive fungal culture allows for exact microbiological determination of the fungal species and for susceptibility testing.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…None of them had undergone lung resection. We and others have previously shown that early lung resection (lobectomy or wedge resection) combined with antifungal therapy is safe, effective, and diagnostic in neutropenic patients suspected of having IPA (1,6,7,8,16,18,26). A positive fungal culture allows for exact microbiological determination of the fungal species and for susceptibility testing.…”
Section: Case Reportmentioning
confidence: 99%
“…A definitive diagnosis of IPA requires a biopsy with histology and fungal culture (21). Early surgical resection combined with antifungal therapy is associated with an acceptable low complication risk, allows identification of the microorganism, and appears to improve the prognosis for patients with localized infections (1,6,7,8,16,18,26).…”
mentioning
confidence: 99%
“…A large majority of all the analyzed articles were dedicated to immunopathology of invasive aspergillosis and study of the fungal virulence, e.g., disease transmission, innate and acquired host-response, genes and proteins involved in fungal invasion, susceptibility to infection: 61.9% addressed this topic vs. 36.1 and 9.3% which were rather devoted to pre-clinical therapy [pharmacology/pharmacokinetics/toxicology, and also several vaccine assays (Clemons et al, 2014) and role of surgery (Habicht et al, 2002)], and to diagnosis/imaging approaches (Yang et al, 2009), respectively. Of note, the analyzed articles frequently covered several research fields at a time: for instance, 10 manuscripts dealt with both diagnosis/imaging and pre-clinical therapy simultaneously, 13 overlapped both diagnosis/imaging and immune-pathophysiology/virulence, and 47 addressed therapeutic and immuno-pathophysiology/virulence concerns within the same studies (Supplementary Material 1).…”
Section: Resultsmentioning
confidence: 99%
“…In this setting, a lobectomy, a segmentectomy, or a wedge resection, depending on the location and size of the aspergillosis lesion may be required [102]. Surgical resection of such lesions appears to improve the outcome [4,[104][105][106][107][108]. However, surgical treatment alone is rarely indicated because the infection is usually bilateral and multifocal.…”
Section: Surgical Treatmentmentioning
confidence: 99%